Outcome following heart transplant assessment in adults with congenital heart disease. Issue 22 (5th July 2019) - Crossland, David Steven; Jansen, Katrijn; Parry, Gareth; Harper, Andrew; Perri, Gianluigi; Davidson, Alison; De Rita, Fabrizio; Hermuzi, Antony; Nassar, Mohamed; Seller, Neil; MacGowan, Guy A; Hasan, Asif; et al.
Abstract : Objectives: Adults with congenital heart disease (ACHD) are a growing group with end-stage heart failure. We aim to describe the outcomes of ACHD patients undergoing assessment for orthotopic heart transplant (OHT). Methods: Case notes of consecutive ACHD patients (>16 years) assessed for OHT between 2000 and 2016 at our centre were reviewed. Decision and outcome were reported as of 2017. Data were analysed in three groups: systemic left ventricle (LV), systemic right ventricle (RV) and single ventricle (SV). Results: 196 patients were assessed (31.8 years, 27% LV, 29% RV, 44% SV). 89 (45%) patients were listed for OHT and 67 (34%) were transplanted. 41 (21%) were unsuitable or too high risk and 36 (18%) were too well for listing. Conventional surgery was undertaken in 13 (7%) and ventricular assist device in 17 (9%) with 7 (4%) bridged to candidacy. Survival from assessment was 84.2% at 1 year and 69.7% at 5 years, with no difference between groups. Patients who were considered unsuitable for OHT (HR 11.199, p<0.001) and listed (HR 3.792, p=0.030) were more likely to die than those who were considered too well. Assessments increased over the study period. Conclusions: The number of ACHD patients assessed for OHT is increasing. A third are transplanted with a small number receiving conventional surgery. Those who are unsuitable have a poor prognosis.